2009
DOI: 10.1029/2008wr006912
|View full text |Cite
|
Sign up to set email alerts
|

Catchments as simple dynamical systems: Catchment characterization, rainfall‐runoff modeling, and doing hydrology backward

Abstract: [1] Water fluxes in catchments are controlled by physical processes and material properties that are complex, heterogeneous, and poorly characterized by direct measurement. As a result, parsimonious theories of catchment hydrology remain elusive. Here I describe how one class of catchments (those in which discharge is determined by the volume of water in storage) can be characterized as simple first-order nonlinear dynamical systems, and I show that the form of their governing equations can be inferred directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
1,342
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 700 publications
(1,390 citation statements)
references
References 85 publications
(112 reference statements)
41
1,342
0
7
Order By: Relevance
“…[21] In this method, the parameters are not optimized globally, but obtained from discharge data from selected periods, following the approach of Kirchner [2009]. From the total data set, periods without P and ET were selected.…”
Section: Methods 2: Recession Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[21] In this method, the parameters are not optimized globally, but obtained from discharge data from selected periods, following the approach of Kirchner [2009]. From the total data set, periods without P and ET were selected.…”
Section: Methods 2: Recession Analysismentioning
confidence: 99%
“…This has been a hydrological research topic for many decades. Brutsaert and Nieber [1977] investigated discharge recession curves, Kirchner [2009] used system parameters obtained with recession analysis in a simple hydrological model, and Teuling et al [2010] used this model to obtain system parameters by means of calibration. There are many other studies in which storage-discharge relations have been found by means of discharge (recession) analysis, but a more obvious approach, namely using storage data directly, is not known to the authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because b 0 is usually close to zero for different solutes, it is possible that the variation in p may be small. Another parameter, b 1 , has been shown to relate storage and discharge in catchments, and is expressed as a function of the parameters k and (Kirchner, 2009; and see Appendix, Equation A12 and A13). The two log-log slopes b 0 and b 1 are not sufficient to uniquely constrain the three parameters k , and p , so the individual e-folding depths (as well as values of the reactivity parameter k R for each solute, see Appendix) could only be determined by direct measurement.…”
Section: Permeability-porosity-aperture Modelmentioning
confidence: 99%
“…The backward difference approximation of dQ/dt (=(Qt-t − Qt)/ t) was calculated using consecutive daily flows and plotted against the arithmetic mean ((Qt-t + Qt)/2) of the corresponding flows [1]. Next, along with simulated actual daily evapotranspiration (AET) from the soil, and infiltration (AI) into the soil-both calculated by the GSFLOW model-recession stream flows were selected according to the following criteria [27][28][29]: (1) data points with no positive values of dQ/dt, and (2) data points when the absolute ratio of (AI-AET) to observed Q is smaller than 0.1. As a result, 51 individual recessions with at least four continuous days' length were derived.…”
Section: Recession Flow Analysismentioning
confidence: 99%